Internationalization of Bangladeshi Banks: What Can We Learn? - Khan, Tasneema; Barua, Bipasha (American Journal of Trade and Policy, 2017)
Internationalization of banking institutions has been more evident to a greater extent recently due to the advancement of technology and global inter-connectedness. As the ‘engine of economic growth,’ banks are the dominant players in Bangladesh financial market. Due to intense competition and quick saturation of the domestic market, banks in Bangladesh are tending to move towards the international market. This research aims to explore the nature and challenges of international banking practices in Bangladesh banking sector, and also to develop the relevant policy perspectives. A semi-structured questionnaire was used to survey top level management of 41 out of total 56 scheduled banks operating in Bangladesh during May 2015. Analyzing the survey, the study finds that Bangladeshi banks do not follow the usual internationalization path, tends to more cost-intensive mode, are in the defensive approach of internationalization, and face several challenges and deficiencies in their current international banking practices. This paper contributes to existing literature by being the first exploring the facet of bank internationalization in Bangladesh and generating new insights for better bank regulation. JEL Classification: M16, M20, N20, F23, G20, L10